Characteristics of Effective Classroom Rules: A Review of the Literature. (May 2017) - Alter, Peter; Haydon, Todd
Difficulty managing classroom behavior is a frequently recognized problem for teachers, especially teachers early in their careers. Classroom rules are identified as an integral part of effective classroom management as they are relatively simple to implement and focus on preventing challenging behaviors before they occur. Sources such as classroom management textbooks and practitioner-oriented journal articles recommend a number of characteristics that make classroom rules effective; unfortunately, these sources have not been uniform in their recommendations. The purpose of this review of effective practices is to compare what information teachers are being given either in their preservice coursework or in-service training via textbooks and practitioner-oriented articles with actual empirical research that used classroom rules as an independent variable. Results indicated that the two most important characteristics of effective classroom rules are teaching the rules to students and tying rules to positive and/or negative consequences. Other characteristics recommended in secondary sources remain equivocal in the research. Implications for effective teacher preparation in classroom management are discussed.